(3NdGUI GdMSGHs
(3ChdgG (B:s
(3fMeOc jG ef dG jMjW GdLeY fYeg YOO hHYO hSejJgG NdGUI GdMSGH hQJHJgG Ydi ebOeI hCHhGH ebOeI GdMSGH Yde jSJYde efg ESJNQGL GdeLghdGJ GdYOOjI s
(3BNQgG (B:s
(3hgcPG abO dGM Hjf gPG hYTQhf UhQI YdjgG JOhQ eSGFd GdEfcSGQ ai gPG GdHGH hgPG GdLOhd cGa ai JhVjM gPG dGLeGd hJfbjM gPg GdCYeGd hai ef Gddg GdYUeI hGdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs